REKRUITMEN TOKOH DALAM MENUJU INDONESIA BERSATU - Subari Subari (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
This work contains an ideal description of prominent figure that is assumed as a proper person to be recruited in the effort of Indonesia unification. Briefly, the topic we will discuss in this paper is dealing with a wish of a few people to return to the past in gaining the prominent figure and the importance of having a leader that respectful with the democratic spirit as a continuing capital in mobilization of whole people’s capability in the direction of Indonesian unification. As a result of the discussion, we will argue that according to the plural condition of Indonesia, the recruitment of a prominent figure should be departed from the smallest rural area that has ability in programming the collaboration with some other areas. The collaboration should be based on the sameness of both vision and mission of his or her political party. But as we have known, most of Indonesian community member knows more about the prominent figure than the vision and mission of political party. Therefore, to win in the local-general election, a political party depends on the influence of prominent figure. Ironically, most of the prominent figure that contribute much in winning the election, he or she is not supported by party’s policy.